Kewenangan Atributif Jaksa dalam Permohonan Pembatalan Perkawinan Tanpa Izin dalam Menjaga Ketertiban Umum - Fadli Rahman Wahidi; Anizar Ayu Pratiwi; Andi Rima Febrina Sari (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2025)
Marriage is a relationship between a man and a woman within a household, legally recognized as husband and wife. The State Attorney (Jaksa Pengacara Negara or JPN), as a functional official, is granted unlimited authority not only in the criminal sphere but also in annulling marriages if they do not have permission according to the provisions of the Marriage Law. The writing methodology in this scientific work is the normative juridical method and library research. This research shows that marriage annulment can be done if the following conditions are not met: the marriage registrar and the person performing the marriage do not have the right or are not authorized, there is still a valid marriage status or the person is in the iddah period when the marriage is performed, there are fewer than two witnesses, the marriage was performed under pressure or threat, and the person is not of legal age to marry according to the law. The role of the prosecutor as a law enforcer and in accordance with statutory provisions gives them authority in civil matters. The prosecutor can file for annulment of the marriage by acting as the petitioner without being required to use a special power of attorney. Keywords: State Attorney; Marriage Without Permission; Marriage Annulment.